CXCL12-CXCR4-Mediated Chemotaxis Supports Accumulation of Mucosal-Associated Invariant T Cells Into the Liver of Patients With PBC - Chen, Zhilei; Liu, Suying; He, Chengmei; Sun, Jinlei; Wang, Li; Chen, Hua; Zhang, Fengchun (Frontiers in Immunology, 2021)
Objectives: To explore the potential role of CD3+CD8+CD161high TCRVα7.2+ mucosal-associated invariant T (MAIT) cells in the pathogenesis of primary biliary cholangitis (PBC). Methods: We enrolled 55 patients with PBC, 69 healthy controls (HCs), and 8 patients with hepatic hemangioma. Circulating MAIT cells and their chemokine receptor profiles and cytokine production were quantified using flow cytometry. Liver-resident MAIT cells were examined by immunofluorescence staining. CXCL12-mediated chemotaxis of MAIT cells was measured using a transwell migration assay. Plasma interleukin (IL)-18 was measured using ELISA, and cytokine production in IL-18-stimulated MAIT cells was detected using flow cytometry. Result: Peripheral MAIT cells were found to be significantly lower in patients with PBC (3.0 ± 3.2% vs. 9.4 ± 8.0%, p < 0.01) and negatively correlated with alkaline phosphatase (ALP) levels (r = −0.3209, p < 0.05). Liver immunofluorescence staining suggested that MAIT cells might accumulate in PBC liver. MAIT cells from patients with PBC expressed higher levels of CXCR4 (84.8 ± 18.0% vs. 58.7 ± 11.4%, p < 0.01), and the expression of CXCL12 was higher in PBC liver. CXCL12 promoted MAIT cell chemotaxis (70.4 ± 6.8% vs. 52.2 ± 3.5%, p < 0.01), which was attenuated by CXCR4 antagonist. MAIT cells from PBC produced significantly more interferon-γ (IFN-γ) (88.3 ± 4.2% vs. 64.2 ± 10.1%, p < 0.01), tumor necrosis factor-α (TNF-α) (93.0 ± 1.1% vs. 80.1 ± 5.3%, p < 0.01), Granzyme B (89.3 ± 3.3% vs. 72.1 ± 7.0%, p < 0.01), and perforin (46.8 ± 6.6% vs. 34.8 ± 7.7%, p < 0.05). MAIT cells from PBC expressed higher levels of IL18-Rα (83.8 ± 10.2% vs. 58.3 ± 8.7%, p < 0.01). Plasma IL-18 was more abundant in patients with PBC (286.8 ± 75.7 pg/ml vs. 132.9 ± 78.1 pg/ml, p < 0.01). IL-18 promoted IFN-γ production in MAIT cells (74.9 ± 6.6% vs. 54.7 ± 6.7%, p < 0.01), which was partially attenuated by blocking IL-18R (68.6 ± 8.3% vs. 43.5 ± 4.2%, p < 0.01). Conclusion: Mucosal-associated invariant T cells from patients with PBC accumulated in the liver via CXCL12-CXCR4-mediated chemotaxis, produced pro-inflammatory cytokines, and contributed to portal inflammation, which was potentially mediated by elevated IL-18. Targeting MAIT cells might be a therapeutic approach for PBC.